Response and resistance to cladribine in patients with advanced systemic mastocytosis: a registry-based analysis: original article - Lübke, Johannes; Naumann, Nicole; Metzgeroth, Georgia; Kreil, Sebastian; Brand, Timo; Horny, Hans-Peter; Sotlar, Karl; Cross, Nicholas C. P.; Fabarius, Alice; Valent, Peter; Hofmann, Wolf-Karsten; Reiter, Andreas; et al. (Annals of hematology, 2023)
We sought to evaluate the efficacy of the purine analogue cladribine in 79 patients with advanced systemic mastocytosis (AdvSM) using data from the ‘German Registry on Disorders of Eosinophils and Mast Cells (GREM)’. The overall response rate according to modified Valent criteria (46 evaluable patients) for first- (1L) and second-line (2L) cladribine treatment was 41% (12/29) and 35% (6/17, P = 0.690), respectively, and the median overall survival (OS, all patients evaluable) was 1.9 years (n = 48) and 1.2 years (n = 31; P = 0.311). Univariate and multivariable analyses of baseline and on-treatment parameters identified diagnosis of mast cell leukemia (hazard ratio [HR] 3.5, 95% confidence interval [CI, 1.3-9.1], P = 0.012), eosinophilia ≥ 1.5 × 109/L (HR 2.9 [CI 1.4-6.2], P = 0.006) and < 3 cycles of cladribine (HR 0.4 [CI 0.2-0.8], P = 0.008) as independent adverse prognostic parameters for OS. There was no impact of other laboratory (anemia, thrombocytopenia, serum tryptase) or genetic markers (mutations in SRSF2, ASXL1 or RUNX1) on OS. In consequence, none of the recently established prognostic scoring systems (MARS, IPSM, MAPS or GPSM) was predictive for OS. Modified Valent criteria were superior to a single factor-based response assessment (HR 2.9 [CI 1.3-6.6], P = 0.026). In conclusion, cladribine is effective in 1L and 2L treatment of AdvSM. Mast cell leukemia, eosinophilia, application of < 3 cycles and a lack of response are adverse prognostic markers.